The Fate of the Czech National from the Standpoint of the Late 1960s: A Few Notes on the Controversy Between Kundera and Havel - Mervart, Jan (Dějiny – teorie – kritika, 2024)
This study attempts to capture the origins of the differences in opinion on the fate of the Czech nation which arose in the period known as the Prague Spring in 1968 as espoused by two of the period´s historical actors, based on an analysis of media sources of the time. Though the controversy was unleashed at the turn of 1969 by Milan Kundera and Václav Havel, other important intellectual figures from Prague and Brno, such as Karel Kosík, Jaroslav Střítecký and Lubomír Nový were eventually to join the fray as well. Within the controversy, two basic approaches may be observed, whose antagonistic tendencies arise out of the generational differences of the participants: the first, represented by Kundera, Kosík and Nový, sees the democratisation experienced in the Prague spring as an integral process within a continuum of Czech history and thus exalt it as a singular process bringing Bohemia once again into a world context; the second approach, however, represented by Havel and Střítecký, looks upon the reform with critical skepticism and refutes the so-called "fate of the Czech nation" (which purports to situate Bohemia in the context of world history) as a fictional construct which takes away the individual´s historical responsibility.